POLITIK LUAR NEGERI DAN PERKEMBANGAN TEKNOLOGI RUANG ANGKASA TIONGKOK 2005-2012 - Desmara, Bobi; Saeri, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This paper explores the intersection of foreign policy objectives and advancements in space technology within the context of China from 2005 to 2012. China's rapid economic growth during this period propelled its ambitions in space exploration and satellite technology, raising significant implications for its foreign policy strategies. This journal will discuss the following topics, History of the development of China's space technology, Factors driving the development of China's space technology, The impact of the development of China's space technology on the country's foreign policy The research methodology involves Journal Internationals and related internet websites to construct a comprehensive understanding of China's pursuit of space capabilities was strategically aligned with its broader diplomatic goals, shedding light on the symbiotic relationship between space exploration and geopolitical aspirations. China's foreign policy in the field of space technology has developed rapidly in recent years. This is marked by the launch of increasingly sophisticated satellites and spacecraft, as well as China's increasing participation in international cooperation in the field of space. Through a comprehensive analysis this study elucidates the ways in which China's space program influenced its regional and global standing. Overall, this paper contributes to a deeper understanding of the nexus between foreign policy and space technology development, with a specific focus on China's strategic trajectory from 2005 to 2012. Keywords : China, Foreign Policy, Space Technology Diplomacy, International Relations and Economic Growth